ANALISIS MONDAY EFFECT DAN ROGALSKI EFFECT TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2013 - Susetriani Putri F.A.S; Syarief Fauzie (Ekonomi dan Keuangan, 2014)
This research aims to test and analyze the Monday effect and Rogalski effect on stock return in Indonesia Stock Exchange. The applied sampling method is purposive sampling. The sample in this research is companies registered as LQ-45 Index during January 2012 up to December 2013. The analysis method applied to analyze the influence factors of return on the trading days is descriptive analysis. The descriptive analysis method is used to depict the daily average of stock returns and monthly stock returns. The hypothesis was tested by Kruskal Wallis Test, Kendall’s Tau, and Wilcoxon Test. The result of hypothesis 1 and hypothesis 2 tests using Kruskal Wallis Test indicates that there is day of the week effect and Monday effect on LQ-45 Index during January 2012-December 2013. The result of hypothesis 3 test using Kendall’s Tau Test indicates that there is not a correlation between Monday effect and bad Friday on LQ-45 Index during January 2012-December 2013. The result of hypothesis 4 test by Wilcoxon Test indicates that there is not Rogalski effect phenomenon on LQ-45 Index during January 2012-December 2013.Keyword: stock return, LQ-45 Index, Monday effect and Rogalski effect